Physical rehabilitation and endothelial dysfunction in coronary heart disease - V. A. Margazin; A. S. Noskova (Кардиоваскулярная терапия и профилактика)
The review contains the data on interaction between physical activity and fitness, from one hand, and principal clinical manifestations of coronary heart disease (CHD), from another hand. Mechanisms of regular training positive effects in heart failure patients are discussed. Physical rehabilitation potential for endothelial function improvement and erectile dysfunction management in CHD are analyzed.